1960
DOI: 10.1021/ac60165a005
|View full text |Cite
|
Sign up to set email alerts
|

A Polarographic Study of Organic Peroxides

Abstract: An improved procedure is outlined for the polarographic study of organic peroxides in a nonaqueous electrolyte solution. Polarograms were observed for 23 commercial organic peroxide compounds having the following functional peroxide groups: hydroperoxides, peroxy acids, peroxyesters, six-membered bicydic peroxides, diacyl peroxides, other diacyl peroxides, and ketone peroxides. Twenty-one of the compounds showed one or more characteristic reduction waves; they were placed in five groups based on different half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1966
1966
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…(1)], 1f reacted with formation of two spin adducts, of which one was assigned to the acyloxyl type and the second one to the alkoxyl type. Separately, it was shown that a few alcohols (19)(20)(21)(22), including methyl benzilate 20, undergo the same type of reaction (Table 2) under similar conditions.…”
Section: Reaction Of Pbn Rcooh and 2 ϩ In Laboratory Lightmentioning
confidence: 96%
See 2 more Smart Citations
“…(1)], 1f reacted with formation of two spin adducts, of which one was assigned to the acyloxyl type and the second one to the alkoxyl type. Separately, it was shown that a few alcohols (19)(20)(21)(22), including methyl benzilate 20, undergo the same type of reaction (Table 2) under similar conditions.…”
Section: Reaction Of Pbn Rcooh and 2 ϩ In Laboratory Lightmentioning
confidence: 96%
“…The reaction between dibenzoyl peroxide and PBN is known to give PhCOO-PBN ؒ in a thermal reaction, assumed to proceed by homolysis of the O᎐O bond of the peroxide and trapping of the benzoyloxyl radical by PBN. 4 However, since dibenzoyl peroxide is a weak electron transfer (ET) oxidant {it has a thermochemically estimated EЊ[(PhCOO) 2 /(PhCOO ؒ PhCOO Ϫ )] of 0.6 V in water and Ϫ0.2 V in a solvent like acetonitrile; 19 a kinetic study of the reaction between dibenzoyl peroxide and a series of hydroquinones in acetonitrile, 20 in combination with the Marcus theory, gave EЊ[(PhCOO) 2 /(PhCOO ؒ PhCOO Ϫ )] = Ϫ0.17 V; an irreversible reduction potential of Ϫ0.1 V in benzene-methanol has been determined; 21 see also below} and is likely to contain and/or form small amounts of benzoic acid or peroxybenzoic acid upon dissolution, it cannot be excluded that the HA catalysed mechanism [eqns. (3)-( 5), with HA = PhCOOH and/or PhCO 3 H and Ox = (PhCOO) 2 ] is the pathway for formation of PhCOO-PBN ؒ .…”
Section: Formation Of Phcoo-pbn ؒ By the Spontaneous Reaction Between...mentioning
confidence: 99%
See 1 more Smart Citation
“…In seeking to obtain information with regard to understanding the mechanisms associated with the ozonation process and formation of organic peroxides, and to develop sensitive and selective methods for this purpose, the approach has been to investigate the utility of electrochemical based techniques, as detection procedures, in conjunction with chromatographic methods of analysis. The literature contains little information with regard to determining organic peroxides using electrochemical based techniques except for polarographic (dc), [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] biamperometric (or dead stop end-point), 23,24 coulometric (controlled-potential), 25 etc., techniques employed more than a quarter century earlier. The high-performance liquid chromatographic (HPLC) determination of organic peroxides and hydroperoxides has been performed with various spectroscopic modes of detection such as UV, [26][27][28][29][30][31][32] IR, 30 NMR, 30 mass spectrometric 30 and chemiluminescence.…”
mentioning
confidence: 99%
“…In neutral solvent the log of the conjugated double bonds versus the half-wave potential (versus mercury pool anode) gave a linear equation, E~ = 2.98 --1.6 log C. A proposed mechanism for the step-wise reduction of conjugated lipids is presented and discussed. polar and nonpolar solvents and a suitable supporting electrolyte, organic polarography has been extended to lipid studies to include both triglyceride and organic peroxides (1,2), steroid (3), and some 'fat-soluble vitamins (4)(5)(6).…”
mentioning
confidence: 99%